2020
DOI: 10.18388/abp.2020_5201
|View full text |Cite
|
Sign up to set email alerts
|

Cis-2 and trans-2-eisocenoic fatty acids are novel inhibitors for Mycobacterium tuberculosis Protein tyrosine phosphatase A

Abstract: Small protein tyrosine phosphatase (PtpA) of Mycobacterium tuberculosis is attributed to the development of latent tuberculosis infection, and hence bocomes an interesting target for drug development. In this communication, inhibition of PtpA by naturally occurring fatty acids cis-2 and trans-2-eicosenoic acid is investigated. Mtb PtpA was heterologously expressed in Escherichia coli, and the activity of PtpA was inhibited by cis-2 and trans-2 eicosenoic fatty acids. Both compunds showed strong inhibition of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It is noteworthy that while we have found two naphthoquinones as inhibitors of Mt-PTPa in this study, earlier studies have identified other compounds that have specific inhibitory effects on Mt-PTPa. Examples include synthetic chalcones [ 65 , 66 ], phenyl azole derivatives [ 67 ], thiosemicarbazides [ 12 ], and Cis-2 and trans-2-eicosenoic fatty acids [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that while we have found two naphthoquinones as inhibitors of Mt-PTPa in this study, earlier studies have identified other compounds that have specific inhibitory effects on Mt-PTPa. Examples include synthetic chalcones [ 65 , 66 ], phenyl azole derivatives [ 67 ], thiosemicarbazides [ 12 ], and Cis-2 and trans-2-eicosenoic fatty acids [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…A lead compound against PtpA, L335-M34 (, ), has an IC 50 of 160 nM and shows significant synergy when used in combination with isoniazid (INH), RIF and pyrazinamide in the guinea pig model [60]. A more recent publication demonstrated that activity of PtpA was inhibited by cis -2 and trans -2 eicosenoic fatty acids, with both compounds showing inhibition of PtpA, with IC50 at 8.20 and 11.26 µM, respectively [63]. Hydrogen bond-mediated binding activity was postulated via in silico modelling.…”
Section: Introductionmentioning
confidence: 99%
“…Thioredoxin reductase (TrxB2), an important protein for oxidative stress defence, is also a substrate of PtkA [ 63 ]. Interestingly, the human homologue, TRXB2, has been speculated to play a major role in oxidative stress (OS) defence during Mtb infection, making compound development against TrxB2 difficult [ 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that cis-2 and trans-2eicosenoic fatty acids can inhibit PtpA (19). A few reports suggest that PtpA and PtpB have common inhibitors, although the inhibitory effect may vary (20).…”
Section: Introductionmentioning
confidence: 99%